Learning the concept of genes, DNA, and chromosome through developed virtual laboratory website - Zydrick L. Avelino (University of Muhammadiyah Malang, 2025)
The study focused on the development of a website that can be used in various fields of science in Junior High School. Particularly, topics that were utilized as part of the re-search report include chromosomes, DNA, and genes for grade 9 learners. This exploratory case study explored learners’ engagement and performance on a developed virtual laboratory website. The results revealed predictors of the implementation that can be associated with the performance of the learners. The data gathered from the responses of learners in the instruments were analyzed through content analysis, correlation, and linear regression. This study can relatively be significant for the teachers of Balanga City to help deliver scientific concepts using simple laboratory experiments combined with the activities within the website. This study is leaning towards a broader range of applications in the schools’ division in the Philippines. The wider implementation may extend help to teachers in the far-flung areas of the country.